O consumo da pirataria na moda de luxo: o espelho de duas faces - Sales, Gabriela Maroja Jales de (2010)
The consumption of piracy in Brazil has grown rapidly, including this country being considered one of the largest consumer markets of counterfeit products in the world. At the same time, Brazil is also one of the top ten luxury markets in the world, producing a contradiction in relation to the luxury fashion products and piracy, arriving on shelves and the consumer's hands almost simultaneously. Some studies have been developed to understand the consumer behavior of piracy, as well as luxury, this relationship was little association. However, this dissertation is proposed to analyze the relationship of consumption of the more privileged classes, such as medium and high, between these two worlds, ie, the luxury fashion and piracy. It starts with the idea that there is a exchange in meaning between the use of piracy in the fashion and the desire to consume luxury legitimate, this disclosed in more detail and commitment to advertising and fast communications, driving the valuation of brands and pushing consumption to stratospheric levels. This survey, conducted in João Pessoa / PB, relied on a method of ethnographic qualitative research with two main data sources: interviews and observation, being the analysis model critical discursive. Were identified as the main motivations for the consumption of luxury fashion piracy the desire to insert themselves in a style of consumption barely accessible even to more economically favored classes, case of those interviewed, the search for beauty and distinction deceptively offered by piracy, since interviewed believed to be consumers of luxury genuine, and hedonism achieved by the experience of buying many items newly introduced in the market and the media for a price much lower to the legitimate, leading them to greater frequency of purchases at a lower cost.